Evaluation Of The Effectiveness Of Angiotensin-Converting Enzyme Inhibitors, Misoprostol, Omeprazole And Their Combinations On The State Of The Gastric Mucous Barrier In Indomethacin Gastropathy In Animals With Experimental Rheumatoid Arthritis (Journal of Pharmaceutical Negative Results, 2022)
AnnotationPurpose. To study the effectiveness of ACEi, misoprostol, omeprazole and their combinations on the state of the gastric mucosal barrier in indomethacin gastropathy in animals with experimental rheumatoid arthritis.Material and methods. Experimental studies were carried out on 78 male rats of mixed population weighing 160-200 g. For experimental studies we used a generally recognized model of experimental rheumatoid arthritis (ERA) in rats, which is carried out by a single injection of 0.2 ml of Freund's adjuvant into the hind right leg. After modeling ERA, NSAID gastropathy was induced in the animals by oral administration of indomethacin at a dose of 2.5 mg/kg. The study was conducted on 13 groups: 1 gr. - intact; 2 gr. animals with ERA; 3 gr. - animals with ERA and indomethacin gastropathy (GERA); 4 gr. - animals with GERA+H2O; 5-9 groups: animals with GERA treated with enalapril, lisinopril, captopril, omeprazole, and misoprostol.Groups 10-13 received a combination of omeprazole with ACEi and misoprostol. Each group consisted of 6 animals. The used drugs were administered for 10 days. The content of mucus-producing cells was calculated by counting the total number of cells in a standard field of view on light-optical preparations under magnification of 40x10.For biochemical studies, animals were slaughtered by one-step decapitation under ether anesthesia, the stomach was extracted, cleaned, washed with cold physiological solution, and the pre-stomach was removed. Then the mucous layer was scraped out, weighed and suspended in distilled water in a porcelain mortar at the rate of 30 mg/ml. The content of sialic acids in the gastric mucosa suspension was determined by the method of L.I. Linevik.Results. In experimental RA (ERA) the content of insoluble glycoprotein (IGP) fractions is practically unchanged.In animals with indomethacin-inducedgastropathyand ERA (GERA) a significant decrease in IGP fractions was observed. In ERA, the number of functioning cells decreased by only 5.8% (p>0.05). In indomethacin-induced gastropathy (GERA), along with a decrease in the content of IGP fractions, there is a significant decrease in the number of functioning mucus-producing cells.ACE inhibitors, omeprazole, and misoprostol have a positive effect on the content of IGP fractions in the gastric mucosa. The use of captopril and misoprostol appeared to be more effective in the treatment of GERA. In the groups with captopril, omeprazole, and misoprostol, the content of functioning cells increased by 82.7%, 68%, and 99.1%, respectively, from that in the GERA group without treatment. Combined use of omeprazole with other drugs potentiates their cytoprotective effect in the form of additive pharmacodynamic interaction. In the groups omeprazole with captopril and omeprazole with misoprostol the drug interaction was more significant. The best results were obtained with the combined use of omeprazole with captopril and omeprazole with misoprostol. In this group, the number of cells increased by 204.2% from that of the group without treatment.Conclusion. In experimental RA the state of the gastric mucosal barrier is practically unchanged. Treatment of RA with indomethacin significantly suppresses the synthesis of insoluble glycoproteins of the mucosal barrier and reduces the number of functioning mucus-producing cells. ACE inhibitors has a cytoprotective effect in the treatment of indomethacin gastropathy. Among them, captopril is more effective, which increases the synthesis of the mucus barrier and the number of mucus-producing cells. By this effect, captopril is equal to omeprazole and misoprostol. When ACE inhibitors and misoprostol are combined with omeprazole, their pharmacodynamic effect increases in the form of additive synergism. Combinations of omeprazole with captopril and omeprazole with misoprostol are the most effective.